The Holistic Components 0f Cattle Production for Solving the Haze In Chiang Mai - Sermkiat Jomjunyong; Wallratat Intaruccomporn (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2019)
Chiang Mai air pollution has persisted in crisis for more than a decade. This issue continues to exist owing to the government has failed in addressing related policies and/or explicit solutions to cope with adopting carrier of farmers. This research found that farmers are familiar with cattle raising because this has been an important part of the country since ancient times. Therefore, cattle production is not only safe economically but also sound indigenously and ecologically. This research was conducted in Mae Chaem District’s Ban Thab Sub-districts of Chiang Mai, where slash and burn corn has been dominant for maize plantation. Participatory Action Research (PAR) was implemented throughout interviewing and observing to collect data from 14 farmers in the selected area. Then the data was analyzed by the inductive approach and descriptive statistics to identify essential components for the sustainability of cattle production. Results yield by the participants indicate that cattle production is the potential to replace slash and burn for monoculture due to its advantages.